Intraoperative consultation with the pathologist (CIP) in thyroid follicular lesions - Delgado, Bolívar; Yametti, Luis; Botta, Fernando (Cirugía del Uruguay, 1992)
A series of 85 follicular lesions studied by the pathologist intraoperatively is analysed. Sensitivity for cancer diagnosis: 100%. Specificity: 95% with positive predictive value of 76.9% and negative one of 100%. lt is concluded that this is a high value study when carried out by a trained pathologist.